2005
DOI: 10.1063/1.1868873
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of c-axis-oriented Ca3Co4O9 thin films on Si (100)

Abstract: Enhanced high temperature thermoelectric properties of Bi-doped c -axis oriented Ca 3 Co 4 O 9 thin films by pulsed laser deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
63
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 11 publications
16
63
0
Order By: Relevance
“…This is very different from the previous TEM analysis of Ca 3 Co 4 O 9 thin films grown on single crystal sapphire (001)-oriented, glass, or (100)-silicon, where the presence of both secondary phases and low-crystallinity structures at the interface were reported. [24][25][26] In our present study, the absence of an amorphous layer close to the interface clearly confirmed the good texture and the epitaxial nature of the Ca 3 Co 4 O 9 thin film with respect to each grain and will be discussed hereafter with respect to the thermoelectric properties. It should be clear that the Ca 3 Co 4 O 9 epitaxial film growth was achieved without the classical substrate-induced epitaxy arising from interactions with low-index surfaces of single-crystal substrates, which is very different from the previous reports.…”
supporting
confidence: 56%
“…This is very different from the previous TEM analysis of Ca 3 Co 4 O 9 thin films grown on single crystal sapphire (001)-oriented, glass, or (100)-silicon, where the presence of both secondary phases and low-crystallinity structures at the interface were reported. [24][25][26] In our present study, the absence of an amorphous layer close to the interface clearly confirmed the good texture and the epitaxial nature of the Ca 3 Co 4 O 9 thin film with respect to each grain and will be discussed hereafter with respect to the thermoelectric properties. It should be clear that the Ca 3 Co 4 O 9 epitaxial film growth was achieved without the classical substrate-induced epitaxy arising from interactions with low-index surfaces of single-crystal substrates, which is very different from the previous reports.…”
supporting
confidence: 56%
“…4͒ and approaches the lattice constant of the CCO349 films prepared by PLD ͑10.70 Å͒, indicating that the derived CCO349 films are in-plane tensile strained. 5,7 A similar shortening of the c-axis lattice constant for all the films suggests that there have been the same inplane tensile stress for all derived films, which can be attributed to the dewetting and will be discussed below.…”
Section: Methodsmentioning
confidence: 85%
“…[1][2][3] The CCO349 is built up by stacking along the c-axis of triple rock salt-type layer Ca 2 CoO 3 and single CdI 2 -type CoO 2 layers, which both have monoclinic symmetry with identical a, c, and ␤, but different b parameters ͑for the Ca 2 CoO 3 layer, a = 4.8376 Å, c = 10.833 Å, ␤ = 98.06°, and b 1 = 4.5565 Å, while for the CoO 2 layer, b 2 = 2.8189 Å͒. 4 As for the fabrication of CCO349 films, which can be used in various applications 5 such as thermochemistry-on-achip, biothermoelectric chips, active cooling for microelectronic processors, and localized cooling/heating at points of interest, the commonly used method is pulsed laser deposition ͑PLD͒, [6][7][8] and there have few reports about the chemical solution deposition ͑CSD͒ route, 9 which is a simple, low-cost method for large-area films. Moreover, in the processes of preparing films, the interfacial strain in the films is a key parameter controlling many physical properties, which has stimulated considerable efforts towards understanding the relaxation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical resistivity (Figure 7a) of the Ca:Co=0.72 film is lower than that of the Ca-rich and Co-rich samples throughout the measured temperature range, owing to its phase purity. The room temperature electrical resistivity of the phase pure sample (6.44 mΩcm) is comparable to most Ca 3 Co 4 O 9 thin films grown by different techniques, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] but somewhat higher than the lowest reported electrical resistivity value for Ca 3 Co 4 O 9 thin films deposited on glass substrates (~4 mΩcm). [ 28 ] The electrical resistivity of the Ca-rich and Co-rich samples increases with increasing deviation of the Ca:Co ratio from the stoichiometric limit, which is attributed to enhanced scattering of charge carriers by the grains of impurity oxide phases.…”
Section: Thermoelectric Propertiesmentioning
confidence: 91%